2017
DOI: 10.1038/s41598-017-07582-1
|View full text |Cite
|
Sign up to set email alerts
|

Allostimulatory capacity of conditionally immortalized proximal tubule cell lines for bioartificial kidney application

Abstract: Novel renal replacement therapies, such as a bioartificial kidney (BAK), are needed to improve current hemodialysis treatment of end-stage renal disease (ESRD) patients. As BAK applications may reveal safety concerns, we assessed the alloimmunization and related safety aspects of readily available conditionally immortalized human proximal tubule epithelial cell (ciPTEC) lines to be used in BAK. Two ciPTEC lines, originally derived from urine and kidney tissue, were characterized for the expression and secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…The concentrations of TNF‐α did not vary in all cases and remained very low (100–300 pg/mL), in agreement with our previous findings (Mihajlovic et al, ; Peters et al, ). If we, however, estimate the absolute amount of TNF‐α in both compartments (based on the volume of each compartment, we observe that the amount of TNF‐α is higher in the extraluminal than in the intraluminal compartment (Figure S3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The concentrations of TNF‐α did not vary in all cases and remained very low (100–300 pg/mL), in agreement with our previous findings (Mihajlovic et al, ; Peters et al, ). If we, however, estimate the absolute amount of TNF‐α in both compartments (based on the volume of each compartment, we observe that the amount of TNF‐α is higher in the extraluminal than in the intraluminal compartment (Figure S3).…”
Section: Resultssupporting
confidence: 92%
“…Besides, the high uraemic toxins concentrations in kidney patients are often associated with inflammation, which may as well be detrimental for the BAK (Hsu et al, ). A first assessment of the immunogenicity of the ciPTEC lines using flat membranes with a small surface area (1.12 cm 2 ) showed that ciPTECs have low immunogenicity in vitro, although able to secrete several proinflammatory cytokines that could potentially mediate a non‐specific inflammatory response (Mihajlovic et al, ). In this work, we investigated whether there is polarization of the production of proinflammatory and immune mediators by the ciPTEC cultured in the BAK system.…”
Section: Introductionmentioning
confidence: 99%
“…Since regeneration and reusability are important factors of an adsorbent, plus the high cost of GO based material 58 , the reusability of GAD hydrogel beads in current study need to considered as well. In this experiment, HCl was chosen as desorbent, the adsorbed Mn(II) can be elute with the treatment of 0.1 mol/l HCl.…”
Section: Resultsmentioning
confidence: 99%
“…The potential utility of IL-6 and IL-8 as in vivo biomarkers of AKI is unclear, but a pilot study that assessed the effects of gentamicin and cadmium chloride on primary proximal tubule cells from two different donors showed greater upregulation of IL-6 and IL-8 than KIM1 levels in response to the compounds 82 . Upregulation of IL-6 and IL-8 expression also occurs in conditionally immortalized proximal tubule cell lines in response to uraemic toxins 93 . Together, these findings suggest that IL-6 and IL-8 are used as readouts of injury in vitro.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%